Applicability of Two Non-Radiographic Mixed Dentition Analysis Methods in Orthodontic Patients - Hafsa Mahida; Sarwat Memon; Maham Khan; Farheen Naz (ziauddin University, 2024)
Background: Using erupted components of a dental arch to estimate the width of the unerupted dental components are the basis of mixed dentition analysis. Non-radiographic mixed dentition analysis employs a regression equation to assess the width of the unerupted canines and premolars. In this study, we assessed the applicability of two non-radiographic methods of mixed dentition analysis in orthodontic patients. Methods: This cross-sectional research was carried out from the records of Ziauddin College of Dentistry, Department of Orthodontics, from November 2019 to March 2020. Pre-treatment dental casts of 120 subjects (60 males and 60 females) aged between 12-30 years undergoing orthodontic treatment were selected. The mesiodistal widths from the left first molar to the right first molar were measured using a digital Vernier caliper on pretreatment dental casts of both arches. Bachman's and Tanaka-Johnston methods were applied to estimate the widths of canine and premolars. Gender dimorphism for actual and estimated values was assessed using an independent sample t-test, which compared the actual and estimated mesiodistal widths of canine and premolar. Results: The actual and estimated widths of canine and premolars reported 14.3±1.4 years for males and 13.4±1.2 years for females. In addition, the Bachman's and Tanaka-Johnston method overestimated the actual widths of unerupted canine and premolar but the difference was statistically insignificant (p≥ 0.05) in both the genders. Conclusion: The two non-radiographic methods were reliable for mixed dentition analysis with minor overestimation between actual and estimated widths (ICC=0.79). This makes both the methods applicable interchangeably in regular clinical practice. Keywords: Mixed Dentition; Unerupted Teeth; Dental Models; Radiography.